Preferences, Continuity, and the Arbitrage Pricing Theory - Jarrow, Robert A. (Review of Financial Studies, 1988)
This article investigates the structure on preferences required to derive Ross's arbitrage pricing theory (APT). It is shown that only ordinal preferences are required. In particular, the APT does not require that agents possess preferences representable as risk-averse expected utility functions. This characteristic of the APT is not shared by the standard equilibrium-based capital asset pricing models.